Asymptotic approach for the nonlinear equatorial long wave interactions - Gutierrez, Enver Ramirez; Dias, Pedro L Silva; Raupp, Carlos [UNESP] (IOP Publishing, 2011)
In the present work we use an asymptotic approach to obtain the long wave equations. The shallow water equation is put as a function of an external parameter that is a measure of both the spatial scales anisotropy and the fast to slow time ratio. The values given to the external parameters are consistent with those computed using typical values of the perturbations in tropical dynamics. Asymptotically, the model converge toward the long wave model. Thus, it is possible to go toward the long wave approximation through intermediate realizable states. With this approach, the resonant nonlinear wave interactions are studied. To simplify, the reduced dynamics of a single resonant triad is used for some selected equatorial trios. It was verified by both theoretical and numerical results that the nonlinear energy exchange period increases smoothly as we move toward the long wave approach. The magnitude of the energy exchanges is also modified, but in this case depends on the particular triad used and also on the initial energy partition among the triad components. Some implications of the results for the tropical dynamics are disccussed. In particular, we discuss the implications of the results for El Nĩo and the Madden-Julian in connection with other scales of time and spatial variability. © Published under licence by IOP Publishing Ltd.
Keywords: Energy exchanges; Initial energy; Long wave equations; Long wave models; Long waves; Long-wave approximation; Non-linear wave interactions; Nonlinear energy exchange; Numerical results; Reduced dynamics; Shallow water equations; Spatial scale; Spatial variability; Time ratio; Tropical dynamics; Typical values; Dynamics; Equations of motion; Nonlinear equations; Wave equations